Use and impact of digital technology in supporting health providers deliver care in low- and low-middle-income countries: A systematic review protocol - Adam T. Craig; Harriet Lawford; Maggie Miller; Liuyi Chen-Cao; Leanna Woods; Siaw-Teng Liaw; Myron A. Godinho (PLoS ONE, 2025)
Background Healthcare providers are critical to the successful, sustainable and impactful implementation of digital health. Despite the growing interest, Digital Health Innovations (DHIs) are often implemented without sufficient evidence, leading to numerous short-lived projects and a limited understanding of their impact on health systems and outcomes. In 2023, the World Health Organization (WHO) introduced a new Classification of Digital Health Interventions, identifying four core DHI user groups. This review aims to synthesise evidence on the impact of DHIs designed for one of these user groups—healthcare providers—on delivering health services in low- and lower-middle-income countries (LLMICs). Methods We will conduct an umbrella review, analysing systematic reviews on DHIs for healthcare providers. Data will be extracted using deductive coding before being thematically analysed according to the 11 DHIs for service providers outlined in the WHO’s 2023 Classification. Discussion This umbrella review will explore, synthesise, and evaluate the quality of evidence on how healthcare providers in LLMICs utilise DHIs to address service delivery challenges and their effectiveness. To our knowledge, this is the first comprehensive synthesis of evidence focused on DHIs designed for use by healthcare providers in LLMICs. It is also the first review to align with WHO’s taxonomy for DHIs, as outlined in the WHO Classification of Digital Interventions, Services and Applications in Health. Systematic review registration The protocol is being registered in PROSPERO (ID: CRD42024586285).